Phospholipase D affects translocation of NPR1 to the nucleus in Arabidopsis thaliana - Janda, Martin; Šašek, Vladimír; Chmelařová, Hana; Andrejch, Jan; Nováková, Miroslava; Hajšlová, Jana; Burketová, Lenka; Valentová, Olga (Frontiers in plant science, 2015)
Phytohormone salicylic acid (SA) is a crucial component of plant-induced defense against biotrophic pathogens. Although the key players of the SA pathway are known, there are still gaps in the understanding of the molecular mechanism and the regulation of particular steps. In our previous research, we showed in Arabidopsis suspension cells that n-butanol, which specifically modulates phospholipase D activity, significantly suppresses the transcription of the pathogenesis related (PR-1) gene, which is generally accepted as the SA pathway marker. In the presented study, we have investigated the site of n-butanol action in the SA pathway. We were able to show in Arabidopsis plants treated with SA that n-butanol inhibits the transcription of defense genes (PR-1, WRKY38). Fluorescence microscopy of Arabidopsis thaliana mutants expressing 35S::NPR1-GFP (nonexpressor pathogenesis related 1) revealed significantly decreased nuclear localization of NPR1 in the presence of n-butanol. On the other hand, n-butanol did not decrease the nuclear localization of NPR1 in 35S::npr1C82A-GFP and 35S::npr1C216A-GFP mutants constitutively expressing NPR1 monomers. Mass spectrometric analysis of plant extracts showed that n-butanol significantly changes the metabolic fingerprinting while t-butanol had no effect. We found groups of the plant metabolites, influenced differently by SA and n-butanol treatment. Thus, we proposed several metabolites as markers for n-butanol action.
Keywords: salicylic acid; phospholipase D; PR-1; n-butanol; metabolome; signaling; NPR1